The role of A-site composition in the photostability of tin–lead perovskite solar cells. Issue 20 (21st September 2022) - Huerta Hernandez, Luis; Haque, Md Azimul; Sharma, Anirudh; Lanzetta, Luis; Bertrandie, Jules; Yazmaciyan, Aren; Troughton, Joel; Baran, Derya
Abstract : The content of methylammonium dominates the photostability of tin–lead perovskite solar cells. Abstract : The efficiency of tin–lead perovskite solar cells (TLPSC) has been consistently increasing. However, their photostability continues to be a persistent challenge. Besides the oxidation of tin (Sn), the presence of methylammonium (MA) has been correlated with poor device photostability, which still remains unclear. In this work, we unravel the influence of the A-site cation choice, MA vs. cesium (Cs), on the photostability and performance of TLPSCs where Cs0.25− x MA x FA0.75 Sn0.5 Pb0.5 I3 (FA: formamidinium; x = 0.0–0.25) is used as a photoactive layer. We observe that the addition of MA ( i.e. increasing x ) improves the device efficiency while reducing the photostability. This reduction is attributed to light-induced interfacial barriers, surface recombination, and ion diffusion. We found that MA volatilizes from the surface of MA-rich devices during illumination, leading to an irreversible performance loss after light exposure. We further demonstrate that MA content rather than the choice of the hole-transport layer (PEDOT:PSS vs. NiO x ) dominates the device photostability. Under continuous 1 sun illumination, devices without MA and with the use of NiO x as a transport layer are able to retain 80% of their efficiency for 690 h, while MA-rich cells retain 80% of their efficiency only for the first 3 h of operation. Our work provides insights into the development of photostable TLPSC.